Islam in the era of globalization : Muslim attitudes towards modernity and identity - Meuleman, Johan H. (RoutledgeCurzon, 2002)
Globalization, modernity and identity are fundamental issues in contemporary Islam and Islamic Studies. This collection of essays reflects the wide diversity that characterises contemporary Islamic Studies. The case studies cover regions stretching from China and Southeast Asia to diaspora communities in the Caribbean and Tajikistan. There is significant participation of intellectual voices from all areas concerned, providing a real contribution to the academic exchange between the Muslim and the Euro-American worlds. [publisher].